PENINGKATAN KEMAMPUAN BERBICARA BAHASA PRANCIS DENGAN MENGGUNAKAN JEUX - Evi Eviyanti (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
The objective of this action research is to find out how to increase the students’ speaking proficiency in French by using games. Games represent one of the teaching techniques which can be used  in teaching Expression Orale II. This research was conducted at French Language Study Programme of Language and Arts Faculty, State University of Medan. The participants of this research were students of the 2007/2008 academic years joining Expression Orale II. The research method used was action research which was conducted in 2 cycles. The proceduresof this action research were planning, acting, observing, reflecting, replanning.The result of this research indicates that after being given the action at cycles 1 and 2, the students’ speaking competence in using French increase step by step.Based on the research, it can be concluded that the use of game in teaching Expression Orale II can increase the students’ French speaking competence.